Are Awaous ocellaris and Belobranchus belobranchus the two species of Nike fish schools ? - Nuralim Pasisingi; Sitty Ainsyah Habibie; Abdul Hafidz Olii (Aceh Journal of Animal Science, 2020)
Investigating goby fish is vital to perform an integrated and comprehensive study in order to maintain the roles of the fish, thus providing balanced ecosystem functions and services, as well as contributing to fish biodiversity. Local societies simply recognize fish species by their local names, which are not common. This condition, in turn, causes hitches in conducting further studies. Nike, the name of a local fish, refers to the schools of goby fish larvae whose adult phase has not been fully confirmed. This study aimed to reveal the species that categorizes as nike fish through tracing adult goby inhabiting freshwater. Two fish samples, i.e., Unknown 01 and Unknown 02, were taken from two sites in Bone River, Gorontalo, Indonesia. These samples were captured purposively using a hand net by considering the morphological similarity between the two target samples and the general characteristic of goby. Furthermore, the samples were analyzed genetically through the PCR sequencing method using the Mitochondrial Cytochrome Oxidase Subunit 1 (CO1) gene. Based on the NCBI database, Unknown 01 had the highest similarity to Belobranchus belobranchus (99.54%), while Unknown 02 was identical with Awaous ocellaris (100%). Unknown 01 and Unknown 02, compared to the BOLD database, the similarity level, had the highest percentage of similarity with B. belobranchus (99.85%) and A. ocellaris (100%), respectively. Therefore, A. ocellaris and B. belobranchus were strongly alleged as two species making up the goby schools in the adult stadia that reach freshwater during their migration.